Professional activity of Polish peri- and postmenopausal women - Żołnierczuk-Kieliszek, Dorota; Janiszewska, Mariola; Mielniczuk, Agata; Dziedzic, Małgorzata A.; Firlej, Ewelina (Menopause Review/Przegląd Menopauzalny, 2016)
Introduction: The menopausal transition as one of the stages in women’s life can bring many ailments which complicate the accomplishment of professional duties. The situation of women on the Polish job market is determined by many barriers and stereotypes which impede women’s access to jobs and professional promotions. Material and methods : The aim of the study was to estimate the professional status and job satisfaction of women aged 40-65. The research was carried out by a survey method, a poll technique in the period from January to March 2016. An original questionnaire consisting of 35 questions was used as a research tool. Results: The analysis of obtained results shows that the arithmetic mean of the age of women in full-time employment was 51.84 years whereas the arithmetic mean of the age of women in part-time or seasonal employment was 52.64. Women aged 45-60 were characterised by a significantly lower job satisfaction than women over 60 years of age. The highest percentage of women in full-time employment lived in large cities. The financial situation of working women determined their job satisfaction. Well-off respondents were more pleased with their jobs than women in a worse financial situation. Conclusions : There is a strong need of education about counteraction of gender and age discrimination on the Polish labour market. The struggle against discrimination requires support on each level of the state administration through the implementation of numerous regulations facilitating the final period and resumption of women’s professional activity.